Traditional clinical symptoms and signs: Kampo pattern diagnosis in modern gastrointestinal disease - Zedler, Paul; Büntzel, Judith; Kuchta, Kenny; Yamaoka, Denichiro; Sato, Nanoha; Watanabe, Kenji; Cameron, Silke (Frontiers in Pharmacology, 2024)
In traditional Japanese Kampo medicine a profound anamnesis is completed by clinical examination. The resulting clinical image forms the basis of the patient's diagnosis pattern including the recent mental, physical and social context. Kampo questionnaires support pattern diagnosis and bridge traditional and Western medicine diagnosis.Traditional Kampo therapy is tailored to a specific body constitution, whilst in Western medicine, the treatment is tailored to a specific disease. The aims of this study were to analyse whether traditional Kampo diagnosis is applicable to German patients and, whether specific symptom patterns are characteristic for defined diseases.This study validates for the first time a Kampo-questionnaire adapted for German patients. The analysis focuses on patients with gastrointestinal diseases, a main field for Kampo medicines.In total, we prospectively included 251 participants, of those 58 were cancer patients (23.1%), 35 had Crohn's disease (13.9%), 18 ulcerative colitis (7.2%), 17 irritable bowel syndrome (6.8%), and 103 other abdominal diseases (41%), as well as 20 German controls (8%). The patient population consisted of 144 female (57.4%) and 107 male (42.6%) participants. The median age was 65 years. Disease duration (average: 211 months) varied from one month (cancer patient) to 540 months (patient with Crohn's disease).The scores from questions on the state of mind were significantly elevated in patients with inflammatory bowel disease (IBD) as well as irritable bowel syndrome (IBS)in comparison to the tumour-and control-groups. This was reflected in questions about abdominal discomfort, appetite, faecal habits, and cold-sensation. Accordingly, symptoms of Qi (i.e. vital energy) deficiency were mostly stated in patients with chronic diseases such as Crohn's disease and ulcerative colitis. Defined symptom combinations did not reflect conventional Western diagnosis.Our results show that symptom patterns are independent of the underlying disease. They rather depict the individual patient within an individual time frame. Traditional Kampo-questionnaires were found to be valid for the analysis of a patients' body constitution (sho) and serve as guide for Kampo treatment. We propose that individual pattern diagnosis should be taken into account to help treatment individualization.